Public Sociology in Lithuania: Pro Et Contra - Poviliūnas, Arūnas (Sociologija. Mintis ir veiksmas, 2009)
Twenty years of the development of sociology after the reestablishment of independence in Lithuania was intensive: the growth of academic field was followed by formation and proliferation of professional identities and the expansion of the professional activities of sociologists. The article on the basis of (1) critical evaluation of the project of public sociology, (2) P. Bourdieu field theory and (3) the experience of the project of the education of the social entrepreneurs aims to discuss the changes of the limits of sociological field and transformations of sociological habitus. The article also discusses the research project of the field of the professional activities of sociologists.